Animasi Pembelajaran Interaktif Microsoft Visual Basic 6.0 Berbasis Flash - Dadi Rosadi; Ridwan Ridwan (Jurnal Computech & Bisnis (e-Journal), 2015)
This paper contains a description of the various media interactive learning which is based on research results in the CV. 4 Vision Media, Media interactive learning is a project for clients who request made interactive media on the CV. 4 Vision Media. In this interactive learning media processing software using Adobe Flash Professional CS6 as the main application and device support software other two are Adobe Photoshop and Corel Draw. Given this media interactive learning, teachers and students can be expected to correlate well to create a harmonious atmosphere between the two sides.  Keywords: media interactive learning